EFFICACY OF LIGATION OF INTERSPHINCTERIC FISTULA TRACT (LIFT) PROCEDURE FOR PERIANAL FISTULA - Sarwat Bibi; Khurram Saqib; Humaira Ahmad; Asif Sagheer (Journal of University Medical & Dental College, 2019)
BACKGROUND: A descriptive, cross sectional study conducted to evaluate outcome of ligation of intersphincteric ﬁstula tract in perianal ﬁstula in terms of procedural safety. METHODS: The purpose of this study is to determine the eﬃcacy of ligation of the intersphincteric ﬁstula tract procedure (LIFT procedure) for the treatment of perianal ﬁstula. The parameters we were concerned about were ﬁstula healing time, presence of recurrence and fecal incontinence. In this study, 50 consecutive cases of perianal ﬁstula underwent ligation of intersphincteric ﬁstula tract. Evaluation of results was done by analyzing data in SPSS V-23. RESULTS: In our study, 42(84%) patients were female. 8 (16%) patients were male. The age of the patients ranged from 20-60 years. 47 (94%) patients developed complete healing with no evidence of recurrence. There were 3 (6%) non-healing cases. The mean healing time was 8 weeks. Anal incontinence didn’t develop in any patient post operatively. CONCLUSION: We have concluded that LIFT procedure is an eﬀective treatment for ﬁstula in ano as there is favourable healing rate with no or very little eﬀect on anal continence. It is eﬀective alternative to other surgical procedures for perianal ﬁstula.